The Human Capital Project - World Bank (World Bank, Washington, DC, 2018)
By improving their skills, health, knowledge, and resilience—their human capital—people can be more productive, flexible, and innovative. Human capital is a central driver of sustainable growth and poverty reduction. Investments in human capital have become more important as the nature of work has evolved. Yet despite substantial progress, significant gaps in human capital investments are leaving the world poorly prepared for what lies ahead. The World Bank Group has launched the Human Capital Project (HCP) to mobilize efforts to address these gaps. The project is intended to raise awareness of the costs of inaction and make the case for investing in people through country engagement and analytical work. The goal of the HCP is a world in which all children arrive at school ready to learn, the time spent in school translates into better learning, and they can grow up to live and work as healthy, skilled, and productive adults. The main text of this volume—which also appears as chapter 3 in the 2019 World Development Report: The Changing Nature of Work —describes the evidence supporting the importance of human capital for people, economies, and societies and lays out the rationale and context for the HCP’s theory of change. The Human Capital Index methodology is detailed in the appendix.